2016
DOI: 10.1039/c6ra24366e
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel smartphone-based application for accurate and sensitive on-field hemoglobin measurement

Abstract: A smartphone-based app for the accurate and sensitive measurement of hemoglobin was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The results of Hb detection show that our cell-phone-based acoustofluidic platform is portable and ready for POC testing, has a low requirement for sample volume (∼10 μL), and provides rapid (∼2 min) and easy readouts. Compared to previous methods, such as spectrophotometric measurement , and cell phone-assisted Hb quantitation, , the LOD of our method for Hb detection is much lower (Table S2). Moreover, our method is more biosafe than the Drabkin colorimetric assay (the international gold standard for Hb quantification), which employs highly toxic reagents (especially potassium cyanide) and generates highly hazardous waste.…”
Section: Resultsmentioning
confidence: 82%
“…The results of Hb detection show that our cell-phone-based acoustofluidic platform is portable and ready for POC testing, has a low requirement for sample volume (∼10 μL), and provides rapid (∼2 min) and easy readouts. Compared to previous methods, such as spectrophotometric measurement , and cell phone-assisted Hb quantitation, , the LOD of our method for Hb detection is much lower (Table S2). Moreover, our method is more biosafe than the Drabkin colorimetric assay (the international gold standard for Hb quantification), which employs highly toxic reagents (especially potassium cyanide) and generates highly hazardous waste.…”
Section: Resultsmentioning
confidence: 82%
“…Smartphones offer an ideal POC platform, as they are already distributed widely worldwide and are in the hands of billions of users across the globe [18]. There has been emerging research on the potential role of smartphones to aid in the estimation of Hgb [19][20][21][22]. In particular, a novel, noninvasive smartphone application (app) described by Mannino, R.G., et al showed initial promising data on accurately measuring blood Hgb concentrations using only an unmodified smartphone [23].…”
Section: Introductionmentioning
confidence: 99%
“…Various biologically derived materials, such as enzymes, cells, nucleic acids, antigen–antibodies, and microorganisms, which could be tested on smartphones. Currently, many researchers have focused on how to combine smartphones and micro-biosensors, micro-bioelectronic mini-devices, microfluidic chips together to achieve real-time, point-of-care, and easy-to-use detections for analytes, especially for clinic and environmental samples [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This has created unexpected opportunities for expanding the diagnostic and the prognostic approach to a large number of pathologies and for evaluating pharmaceutical therapies. With the aid of 3D-print technology, smartphone-based systems with 3D-printed cradles which were used to fix attachments have been explored in diagnostic field [ 8 , 9 , 10 ], food safety [ 11 , 12 ], environmental monitoring [ 13 ] and physical condition [ 3 , 14 ]. Though there are many different biosensor platforms based on smartphones, high-quality camera lenses on smartphones are a critical part and applied extensively for different smartphone biosensor platform.…”
Section: Introductionmentioning
confidence: 99%